Corkscrew esophagus in an elderly patient: A case of diffuse esophageal spasm with literature review - Yasir Kawther Hani Al-Dujaili; Sajjad Ghanim Al-Badri (Radiology Case Reports)
Diffuse esophageal spasm (DES) is a rare motility disorder characterized by uncoordinated esophageal contractions, often presenting with dysphagia and chest pain. This case describes a 70-year-old male who presented with atypical symptoms of DES, including episodic dysphagia to solids, postprandial vomiting, and chest pain triggered by cold liquids. Initially misdiagnosed as indigestion, further evaluation with barium swallow imaging revealed a “corkscrew” esophagus, leading to the diagnosis of DES. The patient's symptoms improved with isosorbide dinitrate. This case underscores the importance of imaging in diagnosing DES, particularly in patients presenting with nontraditional symptoms, and highlights the need for individualized management of this complex disorder.